The Western Karaim Torah A Critical Edition of a Manuscript from 1720 - Németh, Michał (Languages of Asia, 2021)
This volume offers the critical edition and an English translation of the oldest translation of the Pentateuch into Western Karaim copied in 1720 by Simcha ben Chananel (died 1723). The manuscript was compared against several other Karaim translations of the Torah as well as with the standard text of the Hebrew Bible. The author provides a description of the manuscript's language and an outline of the history of Western Karaim translations of the Torah to better understand the its philological and historical background. Readership: All interested in the history of Turkic (especially Kipchak-Turkic) languages and anyone concerned with the Karaim translation techniques of Hebrew religious texts.